Targeting Arginine in COVID-19-Induced Immunopathology and Vasculopathy - William Durante (Metabolites, 2022)
Coronavirus disease 2019 (COVID-19) represents a major public health crisis that has caused the death of nearly six million people worldwide. Emerging data have identified a deficiency of circulating arginine in patients with COVID-19. Arginine is a semi-essential amino acid that serves as key regulator of immune and vascular cell function. Arginine is metabolized by nitric oxide (NO) synthase to NO which plays a pivotal role in host defense and vascular health, whereas the catabolism of arginine by arginase to ornithine contributes to immune suppression and vascular disease. Notably, arginase activity is upregulated in COVID-19 patients in a disease-dependent fashion, favoring the production of ornithine and its metabolites from arginine over the synthesis of NO. This rewiring of arginine metabolism in COVID-19 promotes immune and endothelial cell dysfunction, vascular smooth muscle cell proliferation and migration, inflammation, vasoconstriction, thrombosis, and arterial thickening, fibrosis, and stiffening, which can lead to vascular occlusion, muti-organ failure, and death. Strategies that restore the plasma concentration of arginine, inhibit arginase activity, and/or enhance the bioavailability and potency of NO represent promising therapeutic approaches that may preserve immune function and prevent the development of severe vascular disease in patients with COVID-19.